Unsur Pembentuk dan Makna Idiomatik dalam Rubrik Daerah Surat Kabar Riau Pos: Elements that Form and Idiomatic Meaning in the Regional Column of the Riau Pos Newspaper - Jelia Jelia; Hermandra Hermandra; Mangatur Sinaga (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the elements that form idioms and their idiomatic meanings found in the regional section of the Riau Pos newspaper. The use of idioms in mass media, especially newspapers, plays an important role in enriching language style and conveying information more expressively. However, idioms can also cause misunderstandings because their meanings cannot be understood lexically. Therefore, a study of idiomatic meanings is important. This study uses a qualitative approach with a content analysis method. The data source is news texts from the regional section of the Riau Pos newspaper, published from February 10 to March 10, 2025, in the form of words, phrases, or expressions containing idioms. Data collection techniques involve documentation, reading, and recording, while data analysis includes data reduction, data presentation, and conclusion. The results of the study show that there are 34 idiom data classified into seven constituent elements, namely body parts, five senses, colors, natural objects, animals, plants, and numbers, and idioms are also found that are formed from a combination of two elements. Furthermore, the idiomatic meanings found are contextual and cannot be taken literally; they must be interpreted based on the context in which they are used within the sentence. These findings indicate that idioms in journalistic texts not only function as linguistic variation but also convey messages more effectively, engagingly, and communicatively to readers.